2013
DOI: 10.5194/hess-17-4367-2013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling root reinforcement using a root-failure Weibull survival function

Abstract: Abstract. Root networks contribute to slope stability through complex interactions with soil that include mechanical compression and tension. Due to the spatial heterogeneity of root distribution and the dynamics of root turnover, the quantification of root reinforcement on steep slopes is challenging and consequently the calculation of slope stability also. Although considerable progress has been made, some important aspects of root mechanics remain neglected. In this study we address specifically the role of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(154 citation statements)
references
References 26 publications
(47 reference statements)
4
129
0
2
Order By: Relevance
“…Th is is consistent with the results of Schwarz et al (2013), who indicated that diff erent algorithms (Excel or R) lead to quite different values of the equation parameters and small changes in the fi tting of the root diameter-force curve lead to changes in RBMw model. Th ey stated that power fi tting curves in Excel are not correct.…”
Section: Tensile Strengthsupporting
confidence: 80%
See 3 more Smart Citations
“…Th is is consistent with the results of Schwarz et al (2013), who indicated that diff erent algorithms (Excel or R) lead to quite different values of the equation parameters and small changes in the fi tting of the root diameter-force curve lead to changes in RBMw model. Th ey stated that power fi tting curves in Excel are not correct.…”
Section: Tensile Strengthsupporting
confidence: 80%
“…It is worth mentioning that diff erent methods have been developed to quantify root reinforcement: Wu et al (1979), RipRoot model (Pollen, Simon 2005) and Root Bundle Model (e.g. RBM and RBMw) (Schwarz et al 2013). Among these, Wu et al (1979) model is the simplest and requires minimal parameters (only root tensile strength and the cross-section area of fi bres) but with overestimation in reinforcement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such approaches should be able to account for the different physical contributions of plant root system architectures to slope stability and should also be based on reliable physical modeling of water flow in the soil. For example, the SOSlope model (Schwarz and Thormann 2012;Schwarz et al 2013) implements the 3D spatial heterogeneity of root reinforcement in terms of forcedisplacement under tension and compression. Results enable maps to be created at the hillslope scale for the localization of single shallow landslides, as well as defining the volume of soil mobilized for a given rainfall event.…”
Section: Modelling In Different Dimensionsmentioning
confidence: 99%